Norisoboldine alleviates joint destruction in rats with adjuvant-induced arthritis by reducing RANKL, IL-6, PGE2, and MMP-13 expression - Wei Zhi-feng; Jiao Xiao-lan; Wang Ting; Lu Qian; Xia Yu-feng; Wang Zheng-tao; Guo Qing-long; Chou Gui-xin; Dai Yue (Acta Pharmacologica Sinica, 2016)
Zhi-feng WEI1, Xiao-lan JIAO1, Ting WANG1, Qian LU1, Yu-feng XIA1, Zheng-tao WANG2, Qing-long GUO3, Gui-xin CHOU2, *, Yue DAI1, * 1State Key Laboratory of Natural Medicines, Department of Pharmacology of Chinese Materia Medica, China Pharmaceutical University, Nanjing 210009, China; 2Institute of Chinese Materia Medica, Shanghai University of Traditional Chinese Medicine, Shanghai 201203, China; 3Department of Physiology, China Pharmaceutical University, Nanjing 210009, China Aim: To explore the effects of norisoboldine (NOR), a major isoquinoline alkaloid in Radix Linderae, on joint destruction in rats with adjuvant-induced arthritis (AIA) and its underlying mechanisms. Methods: AIA was induced in adult male SD rats by intradermal injection of Mycobacterium butyricum in Freund’s complete adjuvant at the base of the right hind paw and tail. From d 14 after immunization, the rats were orally given NOR (7.5, 15, or 30 mg/kg) or dexamethasone (0.5 mg/kg) daily for 10 consecutive days. Joint destruction was evaluated with radiological scanning and H&E staining. Fibroblast-like synoviocytes (FLS) were prepared from fresh synovial tissues in the AIA rats. The expression of related proteins and mRNAs were detected by ELISA, Western blotting and RT-PCR. Results: AIA rats, NOR (15 and 30 mg/kg) significantly decreased the swelling of paws and arthritis index scores, and elevated the mean body weight. NOR (30 mg/kg) prevented both the inﬁltration of inflammatory cells and destruction of bone and cartilage in joints. However, NOR (15 mg/kg) only suppressed the destruction of bone and cartilage, but did not obviously ameliorate synovial inflammation. NOR (15 and 30 mg/kg) significantly decreased the serum levels of receptor activator of nuclear factor κB ligand (RANKL), IL-6, PGE2, and MMP-13, but not the osteoprotegerin and MMP-1 levels. The mRNA levels of RANKL, IL-6, COX-2, and MMP-13 in synovium were also suppressed. Dexamethasone produced similar effects in AIA rats as NOR did, but without elevating the mean body weight. In the cultured FLS, treatment with NOR (10 and 30 mmol/L) significantly decreased the secretion of RANKL, IL-6, PGE2, and MMP-13 proteins. Furthermore, the treatment selectively prevented the activation of MAPKs, AKT and transcription factor AP-1 component c-Jun, but not the recruitment of TRAF6 or the activation of JAK2/STAT3. Treatment of the cultured FLS with the specific inhibitors of p38, ERK, AKT, and AP-1 significantly decreased the secretion of RANKL, IL-6, PGE2, and MMP-13 proteins. Conclusion: NOR can alleviate joint destruction in AIA rats by reducing RANKL, IL-6, PGE2, and MMP-13 expression via the p38/ERK/AKT/AP-1 pathway. Keywords: norisoboldine; dexamethasone; rheumatoid arthritis; adjuvant-induced arthritis; joint destruction; fibroblast-like synoviocyte; receptor activator of nuclear factor κB ligand; IL-6; PGE2; MMP-13; COX-2; p38/ERK/AKT/AP-1 pathway This work was supported by the Specialized Research Fund for the Doctoral Program of Higher Education (No 20090096110007), the Innovative Training Plan for Graduate Students of Jiangsu Province (CXLX12_0326) and the Priority Academic Program Development of Jiangsu Higher Education Institutions, and it was partially funded by the Program for Changjiang Scholars and Innovative Research Team in University (IRT1193). * To whom correspondence should be addressed. E-mail yuedaicpu@hotmail.com (Yue DAI); chouguixin@yahoo.com.cn (Gui-xin CHOU) Received 2012-10-04 Accepted 2012-12-14